Creation of the Character of the Devil Boruta in the Drama of Lucjan Rydel “Enchanted Circle” - Wichowa, Maria; Agnieszka Gralak (Diabeł Boruta w dawnej kulturze polskiej, 2021)
Lucjan Rydel, creating the character of Boruta, on the one hand, in accordance with centuries-old tradition, equipped him with typically satanic attributes, on the other hand, he artistically very successfully personalized the hero of his drama. He took into account both Old Polish ideas about Boruta – devil, popular in the nobility (from the second half of the 18th century) and fed his imagination with folk tales in which this devil appeared. It seems that one of the basic sources of the young playwright was the work of Kazimierz W. Wójcicki Klechda, ancient stories and novels of the Polish people and Rus.Rydel created the figure of this devil very ambitiously in artistic terms. He made Łęczyca the devil one of the heroes of his drama, equipped him with a rich psychic life, outstanding intelligence.Boruta in the Enchanted Circle is a highly individualized, fantastic, fairy-tale character and at the same time well set in the realities of the place of action, working freely in the forest, in the forest or at the voivode’s court. Studying the literary creation of this hero, it was shown that Boruta, in accordance with ancient tradition, not only Łęczyca, physically resembles a nobleman. He adopts a deceptive form, here he pretends to be a nobleman, but he fully uses his devils power by turning it against representatives of the nobility. The text of the drama was analyzed showing that Boruta is a master of intrigue and tempter, that he is also a master of lies, it was shown that Rydel emphasized the emphasis on devilish perversity. The author of the drama also wrote that devil is also a tool of punishment in God’s hands. The analysis presented in the paper shows that Rydel, while working on the creation of the character of Boruta, emphasized the individualisation of the hero, the psychological justification of his actions, while the image of his devilish nature was built partly on the knowledge of Old Polish demonology and on the contemporary works of Wójcicki and the monumental studies of Oskar Kolberg.